Transforming BASF into a Learning Organization, Linking the Present with the Future. Issue 1 (January 2015) - Tiwari, Ankita; Prabhu, Kashmeera; Doshi, Rhea
BASF is the world's leading chemical company. The case study is about making BASF (India) into a learning organization. BASF introduced a new competency and performance management framework aiming at changing not only the process but also the way employees think, feel, and act. BASF also had a structured talent development process that identified and developed high potential talent. BASF realized that it was important to challenge the assumptions held by individuals in the organization and create a more open culture. Thus BASF launched the 360 degree initiative for business and functional heads and their senior team. BASF worked on Strategy 2025 and used the bottom-up approach unlike what BASF did in the past. BASF strongly believed that one can learn a lot from others through regular interactions and common goals. BASF realized that learning is a continuous journey with its own challenges. BASF is committed to surge ahead on this path and to continuously innovate and learn in order to provide sustainable solutions and remain a market leader and most important be an admired organization.